Fiscal Policy and Lending Relationships - Melina, Giovanni; Villa, Stefania (Washington, D.C. : International Monetary Fund, 2013)
This paper studies how fiscal policy affects loan market conditions in the US. First, it conducts a Structural Vector-Autoregression analysis showing that the bank spread responds negatively to an expansionary government spending shock, while lending increases. Second, it illustrates that these results are mimicked by a Dynamic Stochastic General Equilibrium model where the bank spread is endogenized via the inclusion of a banking sector exploiting lending relationships. Third, it shows that lending relationships represent a friction that generates a financial accelerator effect in the transmission of the fiscal shock.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet